WILLIS METHOD MODIFICATION WITH A VIEW TO IMPROVING ROUTINE COPROPARASITOLOGICAL DIAGNOSIS - Coêlho, Matheus Diniz Gonçalves; Gonçalves de Faria, Aryadne; Tobias Rodrigues Maciel, Lucas; Alves da Silva-Coêlho, Francine (Revista de Patologia Tropical / Journal of Tropical Pathology, 2019)
Intestinal parasites still cause high morbidity and mortality, due to poor hygiene and sanitary conditions, and therefore indiscriminate treatment has been routine practice advocated by the Public Health staff. Although there is a consensus regarding the need to diagnose such diseases, this is not performed with the necessary care, due to great demand and the lack of a wide ranged and highly sensitive technique. In this sense, most clinical laboratories use routine methods for fecal examination such as the Lutz sedimentation or modified Ritchie methods, which are complete and easy to execute, but do not have adequate sensitivity to detect low density eggs and protozoan cysts, especially when there is a predominance of low parasite burdens. In contrast, there are methods that are based on the flotation of low density developmental forms, namely, the Willis method (NaCl flotation d=1.120), which is rapid, easy to perform and allows high density egg flotation but with low sensitivity for protozoan cysts; and the Faust method, which is based on centrifugal flotation of developmental forms in a 33% ZnSO4 (d=1.200) solution, but with the disadvantage of being lengthy and requiring a centrifuge. In this study, we verified the applicability of introducing an alteration in the Willis method, which consisted in the substitution of NaCl by ZnSO4 in order to combine the advantages of this method with the Faust method. 208 samples were assessed by the Willis and Ritchie methods and by the proposed method (modified Willis). The latter proved superior to the other two (? <0,0001 – X2) regarding the detection of protozoan cysts, but similar to the Ritchie method in regard to other diagnosed parasites, therefore demonstrating the high potential for the introduction of this modified method in the routine of fecal diagnosis.